Herramientas de realidad aumentada para la creación de recursos educativos en la enseñanza del bachillerato técnico en informática en la Unidad Educativa Emiliano Ortega Espinoza en el cantón Catamayo. Año lectivo 2022-2023. - Calle Barba, John Yaco (2024)
Nowadays, new technologies are penetrating sectors that were previously out of reach. A clear example of this can be found in the field of education, where technology has gained notable relevance. One of the main objectives of its implementation in this field is to provide support to both students and teachers. An innovative way to transform the classroom is through the use of tools that foster curiosity for learning, such as Augmented Reality (AR). AR allows the presentation of educational content in an interactive way, making classes more dynamic while simultaneously strengthening both autonomous work and teamwork. The objective of this research is to analyze augmented reality tools for creating educational resources in the teaching of technical high school in computing at the Emiliano Ortega Espinoza Educational Unit, located in the canton of Catamayo, during the 2022-2023 academic year. The population and sample consisted of 16 technical high school teachers from this educational unit; however, on the day the survey was conducted, only 15 teachers participated. A survey technique was used for data collection, employing a questionnaire as an instrument to obtain the necessary information for the project. Additionally, the Likert scale rating was used. The most commonly used tool by teachers is GeoGebra 3D Calculator, with a usage percentage of 33.33%. Keywords: New Technologies, Augmented Reality, Educational Resources, Augmented Reality Tools.